Fatal and non-fatal injury outcomes: results from a purposively sampled census of seven rural subdistricts in Bangladesh - Dr Olakunle Alonge, PhD; Priyanka Agrawal, MPH; Abu Talab, PhD; Qazi S Rahman, MSc; Prof AKM Fazlur Rahman, PhD; Shams El Arifeen, DrPH; Prof Adnan A Hyder, PhD (Elsevier, 2017)
Background: 90% of the global burden of injuries is borne by low-income and middle-income countries (LMICs). However, details of the injury burden in LMICs are less clear because of the scarcity of data and population-based studies. The Saving of Lives from Drowning project, implemented in rural Bangladesh, did a census on 1·2 million people to fill this gap. This Article describes the epidemiology of fatal and non-fatal injuries from the study. Methods: In this study, we used data from the baseline census conducted as part of the Saving of Lives from Drowning (SoLiD) project. The census was implemented in 51 unions from seven purposively sampled rural subdistricts of Bangladesh between June and November, 2013. Sociodemographic, injury mortality, and morbidity information were collected for the whole population in the study area. We analysed the data for descriptive measures of fatal and non-fatal injury outcomes. Age and gender distribution, socioeconomic characteristics, and injury characteristics such as external cause, intent, location, and body part affected were reported for all injury outcomes. Findings: The census covered a population of 1 169 593 from 270 387 households and 451 villages. The overall injury mortality rate was 38 deaths per 100 000 population per year, and 104 703 people sustained major non-fatal injuries over a 6-month recall period. Drowning was the leading external cause of injury death for all ages, and falls caused the most number of non-fatal injuries. Fatal injury rates were highest in children aged 1-4 years. Non-fatal injury rates were also highest in children aged 1-4 years and those aged 65 years and older. Males had more fatal and non-fatal injuries than females across all external causes except for burns. Suicide was the leading cause of injury deaths in individuals aged 15-24 years, and more than 50% of the suicides occurred in females. The home environment was the most common location for most injuries. Interpretation: The burden of fatal and non-fatal injuries in rural Bangladesh is substantial, accounting for 44 050 deaths and 21 million people suffering major events annually. Targeted approaches addressing drowning in children (especially those aged 1-4 years), falls among the elderly, and suicide among young female adults are urgently needed to reduce injury deaths and morbidity in Bangladesh. Funding: Bloomberg Philanthropies.